ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI HARGA SAHAM MELALUI RETURN ON EQUITY SEBAGAI VARIABEL INTERVENING PADA SEKTOR PERTANIAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2017 – 2021 - Muhammad Afifuddin; Ika Wahyuni; Ida Subaida (Fakultas Ekonomi dan Bisnis, 2023)
The agricultural sector is a company that manages and utilizes land to become useful land to meet needs. Companies need a plan in achieving company goals. The company's goal is to maintain profits and better profits to maintain the company's development. The purpose of this study was to analyze and test the Cash Ratio and Debt to Equity Ratio to stock prices in the agricultural sector through Return on Equity. Analysis of hypothesis testing data in this study used the Structural Equation Model - Partial Least Square (PLS-SEM). The results of the direct effect hypothesis test using the PLS 3.0 application show that Cash Ratio has a negative but not significant effect on Return On Equity, Debt to Equity Ratio has a negative but not significant effect on Return On Equity, Cash Ratio has no positive but not significant effect on stock prices, Debt to Equity Ratio has a significant positive effect on stock prices, Return On Equity has a positive but not significant effect on stock prices. The results of the indirect effect hypothesis test show that the Cash Ratio variable has a negative but not significant effect on stock prices through Return on Equity, Debt to Equity Ratio has a positive but not significant effect on stock prices through Return on Equity.